A novel constitutive model for geomaterials in hyperplasticity - Zhang, Zhenguo; Yongqiang Chen; Huang, Zhuping (Computers and Geotechnics, 2018)
This paper proposes a new constitutive model for geotechnical materials that consists two basic constitutive functions, the free energy function and the dissipation rate function, within the framework of hyperplastic theory. This free energy function is capable of describing the pressure-dependent elastic behavior of soils. The new constructed dissipation rate function accounts for the frictional mechanism of energy dissipation. Based on this dissipation rate function, the non-associated flow rule can be obtained. Furthermore, the convexity of the yield surface that is derived from the dissipation rate function is proved. Predictions of the behavior of a soil sample using this new constitutive model agree well with triaxial test data under drained and undrained conditions.